Effects of siRNA-mediated suppression of HPV-11 L1 expression on the proliferation and apoptosis of vaginal epithelial cells - Zeng, Juan (Exp Ther Med, 2017)
The aim of the present study was to investigate the effects of human papillomavirus (HPV) infection on the gynecological disease of vaginitis and to demonstrate how the small interfering RNA (siRNA) method may be used for HPV prevention in the clinic. Human vaginal epithelial cells were transfected with HPV-11 L1 expression vector and siRNA-HPV-11 L1 vectors and a control group was transfected with scrambled siRNA. Cell proliferation in each group was analyzed using the MTT assay and the expression of apoptosis-associated proteins was measured by western blot analysis. Compared with the control group, HPV-11 L1 mRNA and protein levels were significantly increased following transfection with the HPV-11 L1 expression vector in cells (P<0.05), but this result was significantly reversed by silencing of HPV-11 L1 (P<0.05). In addition, cell proliferation in the HPV-11 group was lower than that in the control group; however, cell proliferation was significantly increased in cells transfected with silenced L1 compared with that in the control group (P<0.05). Furthermore, silencing of HPV-11 L1 significantly decreased caspase-3 and caspase-9 expressions in cells, whereas the expression was increased in the HPV-11 L1 group (P<0.05). The present study suggested that siRNA-mediated silencing of HPV-11 L1 may have potential therapeutic applications for treating gynecological diseases associated with HPV-11 infection.